2007
DOI: 10.1002/pssc.200673544
|View full text |Cite
|
Sign up to set email alerts
|

M ‐plane GaN‐based dichroic photodetectors

Abstract: The in-plane asymmetry of M-plane GaN films was used to fabricate polarization-sensitive photodetectors. The measured contrasts between the detected light polarized perpendicular and parallel to the c-axis are as high as 7.25 at 363 nm for a 0.4 µm thick film. For other film thicknesses, the polarization-sensitive bandwidth can be increased. At the same time, the position of the maximum contrast is also affected by the film thickness through a different strain state. Considerations for the detector design show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Besides, the in-plane crystal symmetry can be further reduced by the effect of in-plane anisotropic strain generated by the lattice mismatch between the GaN and the substrate. In particular, the valence band structure of M-plane GaN grown on LiAlO 2 substrates is modified in such a way that the topmost transitions become purely polarized either perpendicular (E ⊥ c) or parallel (E || c) to the c-axis [9,10,81,82]. These properties have been used to fabricate SB as well as MIS polarization-sensitive UV photodetectors [10].…”
Section: Polarization Sensitive Photodetectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the in-plane crystal symmetry can be further reduced by the effect of in-plane anisotropic strain generated by the lattice mismatch between the GaN and the substrate. In particular, the valence band structure of M-plane GaN grown on LiAlO 2 substrates is modified in such a way that the topmost transitions become purely polarized either perpendicular (E ⊥ c) or parallel (E || c) to the c-axis [9,10,81,82]. These properties have been used to fabricate SB as well as MIS polarization-sensitive UV photodetectors [10].…”
Section: Polarization Sensitive Photodetectorsmentioning
confidence: 99%
“…UV PSPD based on M-plane GaN films grown on LiAlO 2 substrates have been recently fabricated [10,81]. These detectors exploit the dichroic properties of strained M-plane GaN films.…”
Section: Polarization Sensitive Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This anisotropic optical response can be used to fabricate polarization sensitive photodetecotors. Recently, Rivera et al [8] have shown that such photodetectors can be fabricated using GaN with improved photoresponse and large polarization selectivity. Here we describe the fabrication and performance of PSPDs based on strained InGaN epilayers grown on GaN/LiAlO 2 substrates.…”
Section: Polarization Sensitive Photodetectorsmentioning
confidence: 98%
“…The specific detectivity in these devices was higher than 5xlO9 cmHz'/2W-' in photovoltaic operation [11]. The maximum sensitivity in the noise measurement was limited by the low parallel resistance of the devices.…”
Section: Device Characterizationmentioning
confidence: 99%